Cardiac arrest in takotsubo syndrome: results from the InterTAK Registry. (16th May 2019) - Gili, Sebastiano; Cammann, Victoria L; Schlossbauer, Susanne A; Kato, Ken; D'Ascenzo, Fabrizio; Di Vece, Davide; Jurisic, Stjepan; Micek, Jozef; Obeid, Slayman; Bacchi, Beatrice; Szawan, Konrad A; Famos, Flurina; et al.
Abstract: Aims: We aimed to evaluate the frequency, clinical features, and prognostic implications of cardiac arrest (CA) in takotsubo syndrome (TTS). Methods and results: We reviewed the records of patients with CA and known heart rhythm from the International Takotsubo Registry. The main outcomes were 60-day and 5-year mortality. In addition, predictors of mortality and predictors of CA during the acute TTS phase were assessed. Of 2098 patients, 103 patients with CA and known heart rhythm during CA were included. Compared with patients without CA, CA patients were more likely to be younger, male, and have apical TTS, atrial fibrillation (AF), neurologic comorbidities, physical triggers, and longer corrected QT-interval and lower left ventricular ejection fraction on admission. In all, 57.1% of patients with CA at admission had ventricular fibrillation/tachycardia, while 73.7% of patients with CA in the acute phase had asystole/pulseless electrical activity. Patients with CA showed higher 60-day (40.3% vs. 4.0%, P  < 0.001) and 5-year mortality (68.9% vs. 16.7%, P  < 0.001) than patients without CA. T-wave inversion and intracranial haemorrhage were independently associated with higher 60-day mortality after CA, whereas female gender was associated with lower 60-day mortality. In the acute phase, CA occurred less frequently in females and more frequently in patients with AF, ST-segment elevation, and higher C-reactive protein on admission. Conclusions: Cardiac arrest is relatively frequent in TTS and is associated with higher short- and long-term mortality. Clinical and electrocardiographic parameters independently predicted mortality after CA.